2012
DOI: 10.5812/aapm.2197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clonidine Premedication on Blood Loss in Spine Surgery

Abstract: Background:Blood loss in spine surgery is an important issue, even though it has been understudied compared with hip and knee arthroplasty.Objectives:In this study, we evaluated the effect of oral clonidine as premedication on blood loss in lumbar spine fusion surgery under anesthesia with propofol and remifentanil.Patients and Methods:In this double-blind, randomized clinical trial, 30 patients who were undergoing lumbar spine posterior fusion surgery due to traumatic fracture were allocated randomly into 2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 27 publications
(21 reference statements)
1
30
0
Order By: Relevance
“…In McClain et al study, SA could reduce the amount of anesthesia drugs, length of surgery time, and other side effects in discus decompression surgery (34). Tetzlaff et al have also shown that in spinal surgeries, SA was a better choice for anesthesia compared to GA resulting in lower side effects (35).…”
Section: Discussionmentioning
confidence: 99%
“…In McClain et al study, SA could reduce the amount of anesthesia drugs, length of surgery time, and other side effects in discus decompression surgery (34). Tetzlaff et al have also shown that in spinal surgeries, SA was a better choice for anesthesia compared to GA resulting in lower side effects (35).…”
Section: Discussionmentioning
confidence: 99%
“…But the results were unsatisfactory. 7 Intravenous clonidine given in dose up to 4 micrograms per kilogram body weight/kg B.W (mics/kg B.W.) had produced satisfactory and reliable hypotension in patients undergoing middle ear and nasal surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…These may affect the duration and technical accuracy of procedures, which are of high importance in spinal surgeries, considering the proximity of operation field to neurological structures (1). Different methods have been used to minimize the operation field hemorrhage, including the use of local vasoconstrictors or inducing deliberate hypotension by means of antihypertensive agents, vasodilators, or the anesthetic drugs (1,2).…”
Section: Introductionmentioning
confidence: 99%